Nilai Pendidikan Karakter pada Novel “I'm Not Stupid” Karya Khusnul Art - Alya Hafizha (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
“The Value of Character Education in the Novel I'm Not Stupid” by Khusnul Art was the primary text used in this research to support the argument that students can benefit greatly from character education programs introduced through literature. Whether it's a result of parents or the environment, the absence of character development in children is the root problem of this research. Thus, character education is crucial for kids, and books are a great way to inculcate these values. Books, whether we know it or not, teach us valuable lessons and entertain us, but they also contain positive messages that can be applied in real life. Reading novels that captivate and motivate youngsters is one approach to help them develop positive character traits. This study recommends reading Khusnul Art's